Cracovian modernists - the 60 ties, 90 ties of the XX century - the returns - Wrana, Jan (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
The European reaction of the leading architects towards the period of international style, “The idea of style has yet again become up-to-date. The modern style, covering the whole world, is uniform and coherent...” [4], promoted at the exhibition “Modernist architecture” organized in Museum of Art in New York by architects Henry Russell Hitchcock and Philips Johnson, was immediate. The leading European architects: a) Walter Gropius wrote: “The aim of Bauhaus was not to promote one particular style...” [4], b) Le Corbusier formulated “Fundamental principles of aesthetics” [4], c) Bruno Taut wrote: “Five assumptions of new architecture” [4]. The message that “The form follows the function” became the very principle of modernism. The year 1972, when the blocks of flats in St. Louis, US were blown up, and the year of the actual end of the ideology originating from CIAM, is the agreed time marked as the end of modernism. It was a few years after Le Corbusier’s death (1965) - the death of the unchallenged spiritual ideologist of modernism.